Valores humanos y su incidencia en el proceso de enseñanza de los estudiantes de la escuela de educación básica Emilio Esparza ciudad de Babahoyo de la provincia de los Ríos - Erazo Ramos, Merly Idania (2017)
This research Word began with the problematic situation that affects the students of the basic education school city of windows as they are low that cannot be recovered in teaching. Headed by the proposed objectives that indicate the correct life where our research is directed, the present research word is based on a theoretical framework. This research also presents a proposal which is alternative to solve the problem posed. Our research is made up of the following the conxeptual framework with is different concepts in what our research is suggested, then the problematic situation presented by the school, the approach of the problem, delimitation of the investigation, the reason for which we perform this work the justification and the objectives as general and specific. The second chapter, we find the theoretical or referential frame that is conformed whit the conceptual frame, the referential frame within this we have the investigative antecedents and the category of analysis, we also find the theoretical position. The hypothesis as much general as the subhipotesis and its variables, the third chapter demonstrates the results of the research in which we find the analysis and interpretation of data obtained by applying it find, conclusions and recommendations both specific and general. The fourth chapter evidences the proposal of application which is composed of the background, the justification, objectives, and the general structure of the proposal, the components and the expected results of the alternative. Being also as last points the bibliography and annexes.